Women’s Role in Central Java Agriculture: A Case Study on Qaryah Tayyibah Peasants Association - Susilowati, Linda; Ismoyo, Petsy Jessy (Yayasan Jurnal Perempuan, 2019)
This research proves the importance of the role of women in the agricultural sector in Central Java through a case study of Peasants Association movement in Qaryah Thayyibah, Salatiga, Central Java. This research uses qualitative methods, with data collection techniques through literature studies, observations, FGDs and in-depth interviews. The analysis technique uses categorization, interpretation and conclusions from the results of data collection. This research shows women have a key role in the development of the agricultural sector. Therefore, SPPQT's programs for empowering women farmers include: (1) women's political education, (2) involvement of women in the Production Community and Farmers Community, (3) Women's involvement in the Village Development Council (Team 11). The findings also showed that there were obstacles in the form of community rejection for the third point. This can be overcome by refer again to SPPQT's vision, gender equality needs to be seen as a solution to improve the agricultural sector.